Maclaurin Coefficient Estimates for New Subclasses of Bi-univalent Functions Connected with a q-Analogue of Bessel Function - Sheza M. El-Deeb (Abstract and Applied Analysis)
In this paper, we introduce new subclasses of the function class Σ of bi-univalent functions connected with a q-analogue of Bessel function and defined in the open unit disc. Furthermore, we find estimates on the first two Taylor-Maclaurin coefficients a2 and a3 for functions in these new subclasses.